39=-7v+4(v+3)

Simple and best practice solution for 39=-7v+4(v+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39=-7v+4(v+3) equation:



39=-7v+4(v+3)
We move all terms to the left:
39-(-7v+4(v+3))=0
We calculate terms in parentheses: -(-7v+4(v+3)), so:
-7v+4(v+3)
We multiply parentheses
-7v+4v+12
We add all the numbers together, and all the variables
-3v+12
Back to the equation:
-(-3v+12)
We get rid of parentheses
3v-12+39=0
We add all the numbers together, and all the variables
3v+27=0
We move all terms containing v to the left, all other terms to the right
3v=-27
v=-27/3
v=-9

See similar equations:

| 50x+3x+2x=2100 | | v/2=7+1 | | 9+3(2x-5)=5x | | 28=-2+5u | | -15g-18=-8-15g | | 7×5^x=31 | | 1x+14=4x-25 | | 2.9=y–6.3 | | 4h−8=3h | | 27y=300 | | 1.1=13.9-4v | | 4-(2x-1)+4x=1 | | 10y=8y+16 | | y-0,75*(y-0,2*y)=235 | | 10v=5v+45 | | (x-14)x=120 | | 26=4(w+7)-6w | | 5x-21=3x-13 | | 2x^-288=0 | | 6n+15=3(2n-5) | | -12x+8=56 | | 3b+15=3(b+5) | | -5x+11=-5x+13+3x | | −6−2s=−6 | | A=6x7 | | (2y-3)-(7y+1)=4 | | 3/x+4=15+5 | | −6−2s=-6 | | /8x+4-2x=52 | | 9k-5=9k-7 | | 7(3x+5)=12-(x+6) | | 2x2−6x−9=0. |

Equations solver categories